Pendeteksi Untuk Tingkat Kemiripan Kata Pada Karya Tulis Ilmiah dengan Menggunakan Metode Nazief Adriani - Arni Damayamti (Graha Mitra Edukasi, 2022)
Scientific writing is a written work that is used to solve problems with scientific methods in which it presents opinions, observations, facts, data, which will produce a written report carried out by a person or in a team by meeting ethical and scientific rules properly. and right. An essay or writing obtained in accordance with its scientific nature and based on the results of observation, review, research in a particular field, compiled according to a certain method with systematic writing in a polite language and its contents can be accounted for for its truth/scientific nature. With the development of communication and information technology that is increasingly rapidly causing the search for information and data is very easy and fast. However, with the development of this technology also causes various negative impacts such as word plagiarism. This study also aims to find the similarity of words or similarity to break words between the input word and the source word. The resemblance is not a synonym, but a word that is close to the actual word, Simmilarity is a very important issue in almost every field of knowledge. The function of Simmilarity is to look for word similarity and word dissimilarity between two observed objects. So with the Nazief-Adriani algorithm, which is used to find basic words in a sentence to be better, the Nazief-Adriani stemming algorithm produces better accuracy when compared to other algorithms because it is caused by various kinds of word variations and combinations of affixes that must be removed for the sake of to get the root word